Modelling and Forecasting Recessions in Oil-Exporting Countries: The Case of Iran - Shahram Fattahi; Kiomars Sohaili; Hamed Monkaresi; Fatemeh Mehrabi (International Journal of Economics and Financial Issues, 2017)
Business cycles show the ups and downs of the national production and can have a great impact on macroeconomic variables. That is why predicting business cycles in macroeconomic is of great importance. Since the main goal of economists is to provide the ground for economic stabilization and to prevent economic fluctuations and instabilities, knowing that the economy has entered a period of economic expansion or recession can be efficient in determining effective economic policies. In this research, using statistical data during 1974-2014 and decision making tree, we tried to forecast the next recessions in Iran. The results show that, among the indicators used, momentum imports, revenue from oil exports, unexpected momentum inflation, real total import, and inflation are more effective in recession forecast.  Also, the results indicate that BRT can be a useful technique for analyzing economic policy.